Aesthetic cognitivism: Towards a concise case for doctoral research through practices in the visual arts. (October 2019) - Riley, Howard
This article addresses a question still frequently posed in the context of UK universities which offer courses in the visual arts: Does the PhD research model of contributing new knowledge fit art, where there are no definitive answers and the main strength of the research is its ability to question?, answering in the positive by distinguishing between propositional knowledge and understanding. It acknowledges the range of work already published on this topic and distils an aesthetic cognitivist position from which the visual arts are construed as powerful means of deepening our understanding, a source of non-propositional knowledge on a par with, although qualitatively different from, the way that the sciences are construed as the means to propositional knowledge. The distinguishing feature of the article is its attempt to provide a relatively concise overview of the background and structure of the case for the inclusivity of research through visual arts practices at doctoral level in the universities, based upon an aesthetic cognitivist position which I hope will support research supervisors and others charged with advocating the viability of practice-based or practice-led doctoral proposals 1 in university cross-disciplinary research degrees' committees.